Bone mineralization and immediate function of six dental implants in patients with Klinefelter syndrome - Galina Ciobanu; Francesca De Angelis; Eugen Slabari; Giorgio Pompa (Clinical Case Reports, 2021)
Abstract Patients with Klinefelter syndrome face many challenges in oral treatment and bone mineralization due to multiple systemic dysfunctions. This case report follows the geometrical treatment with immediate implant loading of an adult male patient with Klinefelter syndrome. Satisfactory results were demonstrated in clinical follow‐up.